2018
DOI: 10.1186/s12245-018-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising fasciitis: a fatal case of sepsis and a diagnostic challenge – case report and review of literature

Abstract: BackgroundNecrotising fasciitis (NF) is a severe, devastating soft tissue infection characterised by rapidly progressing tissue necrosis. This rare condition has a high mortality rate and poses diagnostic and management challenges to the clinician. There is usually a history of trauma, which maybe trivial. Some of the premorbid conditions associated with NF are diabetes and or immunocompromised state. It requires prompt recognition and early treatment with intravenous antibiotics and extensive surgical debride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…59 Thorough clinical examination for sources of sepsis and a low threshold of suspicion for this condition are essential. 5,60 Erythema, warmth, edema, woody induration, pain, and fever may be early signs and can be nonspecific. 51,60 Pain out of proportion and a toxic appearance may be the only distinguishing features at an early stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…59 Thorough clinical examination for sources of sepsis and a low threshold of suspicion for this condition are essential. 5,60 Erythema, warmth, edema, woody induration, pain, and fever may be early signs and can be nonspecific. 51,60 Pain out of proportion and a toxic appearance may be the only distinguishing features at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…It incorporates white blood cell count, hemoglobin, C-reactive protein, sodium, glucose, and creatinine for score computation. 5,60 Scores of 8, 6, and 5 are categorized as high, intermediate, and low risk of NSTIs, respectively. 62 A recent prospective study showed that among patients with duration of symptoms .8 hours, a cutoff score of .4 was reasonably effective in distinguishing necrotizing fasciitis from simple cellulitis, with sensitivity of~85% and specificity of 75%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria isolated from polymicrobial soft tissue infections such as synergistic gangrene and type I necrotising fasciitis include combinations of Gram-positive cocci, Gram-negative bacilli and anaerobes e.g., Bacteroides sp. [35,36]. These infections can result from factors such as infected surgical wounds, burns and chronic skin ulcers, all of which can rapidly progress to polymicrobial sepsis [35,36].…”
Section: Infection Sourcesmentioning
confidence: 99%
“…NF may be caused by a single species of bacteria, or by a polymicrobial variety of microrganisms [ 2 ]. A high index of suspicion is essential as aggressive surgical debridement may be necessary to save life [ 3 ]. NF can develop at sites of skin puncture, surgical wounds, chronic ulcers or insect bites [ 2 ].…”
Section: Introductionmentioning
confidence: 99%